2018
DOI: 10.1111/jnc.14482
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular sorting and transcytosis of the rat transferrin receptor antibody OX26 across the blood–brain barrier in vitro is dependent on its binding affinity

Abstract: The blood–brain barrier (BBB) is a formidable obstacle to the delivery of therapeutics to the brain. Antibodies that bind transferrin receptor (TfR), which is enriched in brain endothelial cells, have been shown to cross the BBB and are being developed as fusion proteins to deliver therapeutic cargos to brain targets. Various antibodies have been developed for this purpose and their in vivo evaluation demonstrated that either low affinity or monovalent receptor binding re‐directs their transcellular traffickin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 35 publications
(60 reference statements)
4
56
0
Order By: Relevance
“…In particular, scFv 46.1 had a unique uptake pattern, namely there were few cytoplasmic 46.1-containing structures and most antibody could be found in puncta at the cell-cell junctions, seemingly distinct from recycling or degradative compartments typical of targeted BBB receptors like the TfR. 43,44 Moreover, confocal microscopy indicated the rapid, vectorial transport of 46.1 from the apical membrane to the basolateral junctions. While the identification of the receptor targeted by 46.1 and the elucidation of the detailed intracellular transport mechanism are the focus of future work, we have not observed any literature describing such an antibody transport profile at the BBB.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, scFv 46.1 had a unique uptake pattern, namely there were few cytoplasmic 46.1-containing structures and most antibody could be found in puncta at the cell-cell junctions, seemingly distinct from recycling or degradative compartments typical of targeted BBB receptors like the TfR. 43,44 Moreover, confocal microscopy indicated the rapid, vectorial transport of 46.1 from the apical membrane to the basolateral junctions. While the identification of the receptor targeted by 46.1 and the elucidation of the detailed intracellular transport mechanism are the focus of future work, we have not observed any literature describing such an antibody transport profile at the BBB.…”
Section: Discussionmentioning
confidence: 99%
“…The short plasma half-life of the sFab OX26-NEP construct is either due to target-mediated drug deposition (TMDD) through TfR on various peripheral cells or a clearance through the glycol-profile on NEP. It was previously shown that a reduction in affinity of a bivalent OX26 was sufficient to prolong the plasma half-life and improve the brain exposure [20]. The longer plasma half-life is likely explaining at least in part the improved brain expose as it provides TfR binders over an extended time period circulating in the peripheral compartment.…”
Section: Plos Onementioning
confidence: 99%
“…Nonetheless, RmAb158-scFv8D3 was preferred due to the efficiency of Aβ reduction. 23) OX26 is the rat TfR bivalent antibody. Its variants, OX26 5 , OX26 76 , OX26 108 , and OX26 174 possess dissociation constant (K d ) values of 5, 76, 108, and 174 nM, against the same single epitope on TfR, respectively.…”
Section: Receptor-targeting Peptides As Ligandsmentioning
confidence: 99%